Analisis Konsep Keterampilan Dasar Layanan Konseling Dalam The Art of Helping karya Robert Carkhuff - Laela, Faizah Noer; Abidati, Athifa Azkial; Ariesta, Devi; Rahmayani, Devina; Azzahrah, Fitri Novalia (Jurnal Bimbingan dan Konseling Islam, 2023)
Basic skills in counseling services are an important foundation that supports an effective and meaningful counseling process. These skills are at the core of interactions between counselors and counselees, helping individuals overcome personal problems, understand themselves, and transform into more positive individuals. Robert R. Carkhuff, a leading figure in the field of counseling, discusses the concept of these basic skills in his book "The Art of Helping". This book provides valuable guidance for counselors in understanding and developing the basic skills necessary to help individuals achieve growth and overcome problems. The concept of basic skills includes aspects such as empathy, active listening, providing constructive feedback, expressing feelings, and facilitating change. This research uses library research and content analysis methods to in-depth understand the concept of basic skills for counseling services according to Carkhuff. The results of the analysis provide insight into how these basic skills can be applied in counseling and their impact on counseling outcomes. Basic counseling skills are an essential element in forming strong relationships and helping individuals achieve positive change. The book "The Art of Helping" remains an important reference in the field of counseling and psychotherapy, providing valuable guidance for counselors and counseling students in developing the self-understanding and skills necessary to help individuals achieve growth and well-being.